Sintered body
By using sintered bodies containing alumina, SiO2 and MnO in the ceramic package and circuit substrate materials, a combination of multiple phases is formed, which solves the problem of high strength and low Young's modulus, and improves the stability of the material and Production efficiency, suitable for miniaturized ceramic components.
Patent Information
- Application Number
- CN202380038439.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-13
- Filing Date
- 2023-06-08
- Publication Date
- 2024-12-17
AI Technical Summary
While sintered bodies of existing ceramic packaging and circuit substrate materials pursue high strength and low Young's modulus, it is difficult to take into account both, and they are prone to damage due to thermal stress during the miniaturization process.
Using a sintered body containing Al2O3, SiO2 and MnO, two glass phases are formed by forming two glass phases, wherein the SiO2 in the first glass phase has a greater proportion of SiO2 and MnO than that in the second glass phase, and a Si-rich phase and a Mn-rich phase are formed. The main crystalline phase of alumina is combined to increase strength and reduce Young's modulus.
It achieves a balance between high strength and low Young's modulus, prevents crack development through glass phases with different toughness, and improves the stability and production efficiency of the sintered body.
Smart Images

Figure CN119156359A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a sintered body containing aluminum oxide. Background Art
[0002] As a material for ceramic packages and circuit boards, aluminum oxide (Al 2 O 3 ) as a main component and containing a sintering aid. As a sintering aid, silicon dioxide (SiO 2 ), manganese oxide (MnO), oxides of 2a group elements, etc.
[0003] As such a sintered body, for example, the following sintered body is known: a main crystalline phase is aluminum oxide, contains 12 mass % to 25 mass % of Mn and Si in terms of oxide conversion, contains a periodic table 2a group element in a ratio of 2 mass % or less in terms of oxide conversion, and the ratio of Mn to Si in terms of oxide conversion is Mn: 2 O 3 / SiO 2 The sintered body is made of alumina raw material powder as a first component and Mn as a second component at a specific ratio. 2 O 3 Powder and SiO 2 The invention discloses a sintered body having a relative density of 95% or more, a strength of 400 MPa or more, a Young's modulus of 300 GPa or less, and a thermal conductivity of 10 W / mK or more. Prior art literature Patent Literature
[0004] Patent Document 1: Japanese Patent Application Publication No. 2003-104772 Summary of the invention Technical problem to be solved by the invention
[0005] Sintered bodies used as materials for ceramic packages and circuit boards preferably have high strength and low Young's modulus. For example, in Patent Document 1, a sintered body having a strength of 400 MPa or more and a Young's modulus of 300 GPa or less is obtained. However, it is desirable to further improve the physical properties of the sintered body.
[0006] In view of this situation, one of the objects of the present disclosure is to provide a sintered body that achieves both high strength and low Young's modulus at a high level. Technical solutions for solving technical problems
[0007] The sintered body of the present disclosure contains Al 2 O3 、SiO 2 and MnO, including Al 2 O 3 The first glass phase is composed of a main crystalline phase, a first glass phase, and a second glass phase having a composition different from that of the first glass phase. 2 The second glass phase is composed of SiO 2 The SiO in the first glass phase is 2 Relative to SiO 2 The total content of SiO and MnO is higher than that of SiO in the second glass phase. 2 Relative to SiO 2 The total content ratio of MnO is high. Effects of the Invention
[0008] According to the above sintered body, it is possible to provide a sintered body capable of achieving both high strength and low Young's modulus at a high level. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 is a schematic cross-sectional view showing the structure of a ceramic package. Figure 2 This is an example of a SEM image of the sintered body according to the present disclosure. Figure 3 This is an image obtained by binarizing the SEM image of the sintered body according to the present disclosure. Figure 4 The SEM image of the sintered body of Comparative Example 2 and the image of the position where the elemental analysis was performed are shown. Figure 5 The SEM image of the sintered body of Comparative Example 4 and the image of the position where the elemental analysis was performed are shown. Figure 6 The SEM image of the sintered body of Example 2 and the image of the position where the elemental analysis was performed are shown. Figure 7 The SEM image of the sintered body of Example 4 and the image of the position where the elemental analysis was performed are shown. Figure 8 The SEM image of the sintered body of Example 6 and the image of the position where the elemental analysis was performed are shown. Fig. 9 The SEM image of the sintered body of Example 8 and the image of the position where the elemental analysis was performed are shown. Fig.10 This is a graph showing the distribution of the Young's modulus and the flexural strength of the sintered bodies of Examples 1 to 8 and Comparative Examples 1 to 5. Fig.11The SiO at each element analysis position of the sintered bodies of Comparative Examples 2, 4, Examples 2, 4, 6, and 8 is shown. 2 Relative to SiO 2 Graph showing the content ratio of total MnO. DETAILED DESCRIPTION
[0010] [Overview of Embodiments] First, the embodiments of the present disclosure are described. The sintered body of the first aspect of the present disclosure includes Al 2 O 3 、SiO 2 and MnO, including Al 2 O 3 The first glass phase is composed of a main crystalline phase, a first glass phase, and a second glass phase having a composition different from that of the first glass phase. 2 The second glass phase is composed of SiO 2 The SiO in the first glass phase is 2 Relative to SiO 2 The total content of SiO and MnO is higher than that of SiO in the second glass phase. 2 Relative to SiO 2 It should be noted that in this application, the glass phase includes SiO 2 In addition to the glass components of Mn and MnO, a certain amount of crystalline components of the ceramic component contained in the sintered body may be contained.
[0011] The miniaturization of electronic devices such as smartphones and wearable devices continues to develop. Along with this, it is also required to miniaturize components such as ceramic packages installed in the equipment. On the other hand, if the components are made thin-walled and low-thickness in order to promote miniaturization, the physical strength will be reduced, which becomes a problem. For example, if a ceramic package is joined to a cover for airtight sealing, the thermal stress caused by the difference in thermal expansion coefficient between the package and the cover sometimes causes the package to be damaged. Therefore, studies have been conducted to improve the strength of ceramics. On the other hand, it is also known that from the perspective of relieving stress, the lower the Young's modulus of the ceramic, the more preferred it is.
[0012] The inventors of the invention have repeatedly studied sintered bodies containing a main crystalline phase composed of aluminum oxide and a glass phase. Then, they found that there is a method for producing a sintered body containing SiO in addition to aluminum oxide. 2 It was found that two glass phases are formed in a sintered body of SiO and MnO, and that the sintered body containing the two glass phases has both high strength and low Young's modulus at a higher level than before. 2 Relative to SiO 2The total content ratio of SiO and MnO is different. 2 The content ratio of SiO in the second glass phase is 2 More specifically, it was found that the first glass phase is SiO 2 Relative to SiO 2 The second glass phase is a phase in which the total content of SiO and MnO is 65 mass % or more and less than 100 mass % (hereinafter sometimes referred to as Si-rich phase), and the second glass phase is SiO 2 A phase having a content ratio of 35 mass % or more and less than 65 mass % (hereinafter, sometimes referred to as a Mn-rich phase).
[0013] Although not bound by a particular theory, it is believed that the sintered body of the present disclosure has three phases with different toughnesses mixed together, which may be one of the main reasons for achieving both high strength and low Young's modulus. It is believed that in the sintered body of the present disclosure, the main crystalline phase composed of aluminum oxide has relatively lower toughness than the glass phase, and SiO 2 The first glass phase with a higher content ratio has higher toughness than the second glass phase. If stress is applied to the sintered body, the aluminum oxide phase with the lowest toughness will first produce tiny cracks. If the development of the cracks spreads to most of the sintered body, the sintered body will be damaged. On the other hand, if the extended cracks reach the glass phase with higher toughness than aluminum oxide, the development of the cracks may be suppressed. Here, it can be considered that the existence of two phases with different toughness as glass phases has an excellent effect of preventing the development of cracks, and both high strength and low Young's modulus can be taken into account.
[0014] Whether the sintered body contains a main crystalline phase composed of aluminum oxide, a first glass phase, and a second glass phase can be confirmed by, for example, identifying the three phases in a SEM image of a cross section of the sintered body and performing elemental analysis on each phase.
[0015] In the sintered body of the present disclosure, SiO 2 The total content of SiO and MnO with respect to the total mass of the sintered body may be 11.0 mass % or more and 30.0 mass % or less. 2 Relative to SiO 2 The total content of MnO may be 54.0 mass % or more and 66.6 mass % or less. When the content of the glass phase in the sintered body is within the above range, both high strength and low Young's modulus can be achieved, and the sintered body can be produced stably and efficiently.
[0016] The area ratio of the first glass phase, obtained by binarizing the scanning electron microscope image of the alumina sintered body, may be 0.1 area % or more and 10 area % or less with respect to the sintered body. The area ratio of the second glass phase, obtained by binarizing the scanning electron microscope image of the alumina sintered body, may be 10 area % or more and 30 area % or less with respect to the sintered body.
[0017] The content ratio of each phase contained in the sintered body is obtained by observing the cross-section of the sintered body using a scanning electron microscope (SEM). In the SEM image, the main crystalline phase, the first glass phase, and the second glass phase are identified as three phases of different shades. The content ratio is calculated based on the area occupied by each phase in the image after binarization processing.
[0018] In the sintered body of the present disclosure, in addition to the SiO 2 In addition to the second glass phase having a content ratio of 35 mass % or more and less than 65 mass %, SiO 2 By forming the first glass phase at 0.1 area % or more, the effect of the first glass phase can be obtained, and a sintered body having both high strength and low Young's modulus can be obtained.
[0019] [Specific example of embodiment] Next, specific embodiments of the sintered body according to the present disclosure will be described.
[0020] (Sintered body) The sintered body of the present disclosure is a solid material obtained by sintering a ceramic material such as alumina powder. The sintered body is typically obtained by sintering a green sheet obtained by molding ceramic material powder into a strip shape or a compact obtained by compacting ceramic material powder.
[0021] (Structure of sintered body) The sintered body of the present disclosure includes a crystalline phase and two glass phases. In the sintered body of the present disclosure, the aluminum oxide phase, the first glass phase, and the second glass phase are randomly mixed without any specific regularity. The aluminum oxide phase, the first glass phase, and the second glass phase are phases characterized by their composition, and are identified as three different portions of light and dark in an image (SEM image) obtained by observing a cross section of the sintered body with a scanning electron microscope.
[0022] exist Figure 2 An example of a SEM image of the sintered body according to the present disclosure is shown in FIG. Figure 2In the SEM image, the aluminum oxide phase 11 of the sintered body 100 is observed as an opaque gray portion. In the SEM image, the aluminum oxide phase 11 is mainly observed as a form in which many particles are connected and continuous at the interface. A part of the aluminum oxide phase 11 is observed as an independent granular form. The form of the aluminum oxide phase in the sintered body is not limited to Figure 2 In the example shown, the particles may be more closely connected to each other, or a form may exist in which many independent particles exist.
[0023] In the SEM image, the first glass phase 21 of the sintered body 100 is darker than the alumina phase 11. In the SEM image, the first glass phase 21 is typically observed as an amorphous granular form. The first glass phase 21 is not limited to granular form, but may also be an amorphous continuous shape. The size of the particles constituting the first glass phase 21 is not particularly limited. As an example, when the particles constituting the first glass phase 21 are assumed to be the smallest quadrilateral S surrounding the particles, the proportion of particles whose side length of the quadrilateral S does not exceed 5 μm in the first glass phase is 50% or more, preferably 80% or more.
[0024] In the SEM image, the second glass phase 31 of the sintered body 100 is lighter in color than the alumina phase 11. In the SEM image, the second glass phase 31 typically has a form obtained by solidifying a material cast in a manner that fills the gaps in the alumina phase 11. The second glass phase 31 is observed as an amorphous portion extending in a manner that surrounds the alumina phase 11 and the first glass phase 21. In the sintered body involved in the present disclosure, two glass phases exist, thereby filling the gaps in the alumina phase 11 that exists in a granular or joined granular form. The second glass phase 31 exists in the sintered body as an amorphous network portion.
[0025] In the SEM image, black portions are observed as voids 51 .
[0026] The content ratio of the first glass phase and the second glass phase in the sintered body is represented by the value (area %) obtained by converting the SEM image of the sintered body into black and white using image processing software and calculating the area ratio of each of the first glass phase 21 and the second glass phase 31 relative to the overall area of the image. The specific calculation method is described as follows, for example. That is, an SEM image of the sintered body to be calculated is prepared, and for the image, a histogram is represented with the horizontal axis being the brightness value (for example, 0 to 255) and the vertical axis being the frequency of occurrence. Next, with reference to the image, a threshold value for the brightness value of each phase that divides the void, the first glass phase, the alumina phase, and the second glass phase is determined. After the threshold value is determined, the integral value of the frequency of occurrence in each partition is calculated, and the proportion of the integral value of each partition relative to the integral value of the frequency of occurrence in the total brightness value is determined. As image processing software, for example, well-known software such as "ImageJ" can be used. Figure 3Through the above method Figure 2 The SEM image is binarized to extract the first glass phase 21 and the second glass phase 31 . Figure 3 The left side is a binary image of the first glass phase (black is the first glass phase, and white is other phases), and the right side is a binary image of the second glass phase (black is the second glass phase, and white is other phases).
[0027] The sintered body involved in the present disclosure preferably has a first glass phase content of 0.1% by area or more and 10% by area or less based on the content calculated by the above-mentioned binary analysis. It is believed that by containing 0.1% by area or more of the first glass phase, the effects of the present disclosure such as high strength and low Young's modulus can be obtained. In addition, when the content of the first glass phase is 10% by area or less, a sintered body with excellent stability during manufacturing and high production efficiency can be obtained.
[0028] The sintered body disclosed herein preferably has a second glass phase content of 10% by area or more and 30% by area or less based on the content calculated by the above-mentioned binary analysis. When the second glass phase content is 10% by area or more, a dense ceramic having excellent sinterability is formed. If the second glass phase content is 30% by area or less, a sintered body having excellent stability during manufacturing and high production efficiency can be obtained.
[0029] The relative ratio of the first glass phase and the second glass phase is not particularly limited. For example, the content ratio of the first glass phase can be 0.3 area % or more and 50 area % or less relative to the sum of the content ratios of the first glass phase and the second glass phase. In the conventional sintered body, only the second glass phase is generated. In contrast, in the sintered body involved in the present disclosure, in addition to the second glass phase, the first glass phase having a high Si content is also included. It is believed that the effect brought about by the presence of the first glass phase at a first area % or more in the glass phase can be obtained.
[0030] (Composition of sintered body) As described above, the sintered body according to the present disclosure includes at least three phases. Hereinafter, the compositions of the crystal phase and the glass phase of the sintered body according to the present disclosure will be described.
[0031] In the sintered body of the present disclosure, the crystal phase includes Al 2 O 3The main crystalline phase (hereinafter, sometimes referred to as the alumina phase) constituted by the sintered body may be only the alumina phase, or may contain other crystalline phases. For example, in the case where the sintered body contains Mo as a colorant, in addition to the alumina phase, it may also contain a Mo crystalline phase. It may also further contain one or more crystalline phases other than them. In the case where the crystalline phase contains the alumina phase and phases other than this, the content ratio of the alumina phase relative to the entire crystalline phase is not particularly limited, for example, preferably 50 volume % or more.
[0032] The sintered body of the present disclosure includes at least two glass phases with different compositions as the glass phase. Here, "different compositions" means that at least one of the type and content ratio of the composition constituting the glass phase is different. The glass phase includes SiO 2 Next, the two glass phases are described separately.
[0033] The first glass phase contains SiO 2 and MnO, is SiO 2 Relative to SiO 2 The total content of SiO and MnO is 65 mass % or more and less than 100 mass %. 2 Relative to SiO 2 The total content of SiO and MnO is more preferably 75% by mass to 99% by mass. 2 The content ratio of Si atoms and MnO is calculated from the measured values obtained by elemental analysis of the glass phase, and the content ratio is converted into SiO 2 Compared with the second glass phase, the first glass phase has a larger SiO 2 For example, SiO in the first glass phase 2 The content ratio of SiO in the second glass phase 2 The content ratio of may be 1.2 times or more, more preferably 1.5 times or more.
[0034] The elemental analysis of the glass phase can be measured using a known analysis method such as scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX), fluorescent X-ray analysis (XRF), and inductively coupled plasma atomic emission spectrometry (ICP-AES).
[0035] The second glass phase contains SiO 2 and MnO, is SiO 2 Relative to SiO 2 and MnO in a total content ratio of 35 mass % or more and less than 65 mass %. In the second glass phase, SiO 2 Relative to SiO2 The total content of Mn and MnO is more preferably 40% by mass to 60% by mass.
[0036] The first glass phase and the second glass phase may be composed only of SiO 2 and MnO, and may also contain SiO 2 As components other than SiO 2 There is no particular limitation on components other than MnO as long as the effects of the present disclosure can be obtained.
[0037] The content ratio of each component constituting the sintered body having the above structure can be, for example, in the following ranges. ·Al 2 O 3 : 70.0 mass % or more and 89.0 mass % or less relative to the total mass of the sintered body ·SiO 2 : 5.7% by mass or more and 20.0% by mass or less relative to the total mass of the sintered body MnO: 3.7% by mass or more and 11.0% by mass or less relative to the total mass of the sintered body
[0038] In the sintered body of the present disclosure, SiO 2 The total amount of Mn and MnO (total of mass) relative to the mass of the entire sintered body can be 11.0 mass % or more and 30.0 mass % or less, and more preferably 11.8 mass % or more and 24.4 mass % or less. If it is less than 11.0 mass %, two glass phases cannot be formed, and if it is greater than 30 mass %, it is easy to adhere to the setter during firing, making it difficult to obtain a sintered body with high production efficiency.
[0039] In the sintered body of the present disclosure, SiO 2 Relative to SiO 2 The total ratio of MnO can be 54.0 mass % or more and 66.6 mass % or less, and more preferably 56.0 mass % or more and 62.9 mass % or less. It is found that if it is less than 54.0 mass %, two glass phases are not generated in the sintered body, and if it is greater than 66.6 mass %, it is difficult to form a dense sintered body.
[0040] The sintered body according to the present disclosure may be composed only of the above-mentioned components and inevitable impurities, and the inevitable components may be contained in an amount of 0.1 wt % or less in terms of oxides, for example.
[0041] (Physical properties of sintered body) The strength of the sintered body disclosed in the present invention can be set according to the application, and can be 300 MPa or more, and more preferably 400 MPa or more. It should be noted that the "strength" mentioned in this specification refers to the so-called bending strength, which is the average value of the values measured at room temperature according to the three-point bending test method based on JIS R1601 (bending test method for fine ceramics). The higher the strength, the more preferred, but as the strength increases, the Young's modulus also increases. In a graph ( Fig.10 ), the coordinates of the strength and Young's modulus of the sintered body may exist between the straight line y=1.7x+18 and the straight line y=1.7x+168. Therefore, the strength may be 660 MPa or less, more preferably 600 MPa or less.
[0042] The Young's modulus of the sintered body disclosed in the present invention can be set according to the purpose, and can be 290GPa or less, and more preferably 280GPa or less. The Young's modulus is the average value of the value measured at room temperature according to the measurement method measured by a strain gauge based on three-point bending of JIS R1602. The lower the Young's modulus, the better, but as the Young's modulus decreases, the strength also decreases. In a graph with the vertical axis, i.e., the y-axis, as the strength (unit: MPa) and the horizontal axis, i.e., the x-axis, as the Young's modulus (unit: GPa), between the straight line y=1.7x+18 and the straight line y=1.7x+168, there can be coordinates of the strength and Young's modulus of the sintered body. Therefore, the Young's modulus can be above 170GPa, and more preferably above 190GPa.
[0043] The porosity of the sintered body is not particularly limited. For example, when the sintered body is used in a ceramic package for sealing an oscillator or a semiconductor element, the porosity is preferably 3% by area or less. In addition, when the sintered body is used in a ceramic package for sealing an optical semiconductor element, the porosity is preferably 3% by area or more and 8% by area or less. The porosity is a value obtained by photographing a cross section of the sintered body with a scanning electron microscope, binarizing it with image processing software, and measuring the area ratio occupied by the voids.
[0044] (Method for producing sintered body) When the sintered body according to the present disclosure constitutes a ceramic package, it can be manufactured, for example, by the following method. First, a green sheet preparation step is performed. Specifically, Al, which is the main component of the sintered body, is milled by a ball mill. 2 O 3 Powder, SiO as sintering aid 2 Powder, Mn compound powder, resin, solvent, etc. are mixed to obtain a paste. As the Mn compound, a Mn salt is preferably used, and specifically, MnCO is preferably used. 3The paste is processed into a raw sheet by a scraper method. The shape of the raw sheet can be determined according to the shape of the target component. For example, in the case of forming the bottom wall portion of the package or the circuit substrate, a raw sheet with a rectangular plane shape is prepared. In the case of forming the frame portion of the package, a ring-shaped raw sheet with the portion corresponding to the cavity removed is prepared.
[0045] Next, a conductive portion printing step is performed. In this step, a paste to be a conductive portion is printed on the green sheet prepared in the previous step. Specifically, at least one metal powder of W, Mo and Cu, an additive, a resin, a solvent, etc. are first mixed, and ceramic powder is further added as needed, and kneaded to prepare a paste.
[0046] For example, the paste is printed on the raw sheet prepared in the previous process by screen printing. For example, in the case where the raw sheet will become the bottom wall of the ceramic package, the conductive portion paste is printed in the area corresponding to the external terminal. Similarly, the conductive portion paste is printed at a position corresponding to the final shape. After printing the conductive portion paste, the raw sheet is dried. Drying can be carried out, for example, by heating to 110° C. and maintaining it for 5 minutes. After drying, the raw sheets are stacked to obtain a raw sheet stack.
[0047] Next, a firing step is performed. In this step, the stack of green sheets prepared in the previous step is fired. The firing can be performed, for example, by heating to a temperature of 1150° C. or higher and 1300° C. or lower in an atmosphere mixed with hydrogen, nitrogen, and water vapor. The firing temperature is more preferably 1200° C. or higher and 1250° C. or lower. It is believed that when firing is performed within this temperature range, there is a high tendency to form a glass phase with two phases of different compositions.
[0048] (Application of sintered body) The use of the sintered body according to the present disclosure is not particularly limited, but as one of the specific uses, it can be used as a component constituting a package that accommodates a chip such as a crystal oscillator. Figure 1 1 is a cross-sectional view schematically showing the structure of a crystal oscillator using a sintered body according to the present disclosure. The crystal oscillator 1 has a package 101, a crystal blank 201, a solder 301, and a lid 401. A cavity CV is provided in the package 101. The crystal blank 201 is accommodated in the cavity CV. The crystal blank 201 is mounted on an element electrode pad 111 of the package 101. The package electrode pads 112 and 113 are arranged on the base 100 outside the cavity CV.
[0049] The base 100 of the package 101 is made of the sintered body (ceramic) of the present disclosure. The base 100 includes a substrate portion 110 and a frame portion 120. The substrate portion 110 forms the bottom surface of the cavity CV. The frame portion 120 is Figure 1 The substrate portion 110 is stacked on the substrate portion 110 in the longitudinal direction (in the longitudinal direction).
[0050] The cover 401 is bonded to the metallization layer 600 of the package body 101 via the solder 301. The cover 401 and the package body 101 are bonded via the solder 301 to seal the cavity CV. The solder 301 typically preferably contains an alloy containing gold, for example, an alloy containing gold and tin (Au-Sn alloy). The cover 401 contains metal, for example, an alloy containing iron and nickel.
[0051] The metallization layer 600 includes, for example, a metal containing at least one of molybdenum (Mo) and tungsten (W). A plating layer, typically a gold plating layer, may be provided on the surface of the metallization layer 600 (the surface facing the solder 301). A nickel plating layer may be provided as a base for the gold plating layer.
[0052] The sintered body of the present disclosure is suitable for use as a material for various ceramic packages, such as a ceramic package for sealing semiconductor elements such as a CMOS image sensor, a ceramic package for sealing optical semiconductor elements, and a circuit substrate. It should be noted that the shape of the sintered body of the present disclosure can be various shapes depending on the application. The shape in the case of a package is as described above. In addition, the sintered body of the present disclosure can also be in various shapes such as a plate, a rectangular parallelepiped, and a film.
[0053] [Example] Sintered bodies according to Examples 1 to 8 and Comparative Examples 1 to 5 were produced and their morphologies were observed. In addition, the strength and Young's modulus of the sintered bodies were measured. (Sample production) Alumina powder with an average particle size of 1.8 μm and MnCO powder with an average particle size of 3.5 μm were used. 3 Powder, SiO with an average particle size of 1.2 μm 2 The powders were mixed in the ratios shown in Table 1 to obtain mixed powders. Table 1 shows the input amount (mixing ratio) of each powder and the calculated value based on the input amount (MnCO 3 The value converted to MnO). It should be noted that in Example 7, MoO 3 When the total of the above three powders is set to 100 mass%, MoO 3 The amount of powder added was 0.5 mass %. Furthermore, Table 1 shows that MnCO 3 Converted to MnO value, SiO 2 Together with MnO, SiO 2 Relative to SiO 2 The total content of SiO and MnO. 2 Relative to SiO 2 The total content ratio of SiO and MnO is expressed as 2 / (SiO 2 +MnO).
[0054] The obtained mixed powder was mixed with polyvinyl butyral, a tertiary amine, and phthalate (diisononyl phthalate: DINP) as organic components, and further mixed with IPA (isopropyl alcohol) and toluene as solvents to prepare a paste.
[0055] Using the prepared paste, a ceramic tape with a thickness of 50 μm to 400 μm is produced by a scraper method. The obtained ceramic tape is cut into pieces of 50 mm in length and 50 mm in width, arranged on a Mo-made firing support plate, and fired at a firing temperature (maximum temperature) shown in Table 1 for 2 hours in an atmosphere of a mixture of hydrogen, nitrogen and water vapor with a dew point of 35°C. 100 sintered bodies of each of Examples 1 to 8 and Comparative Examples 1 to 5 are produced. It should be noted that the temperature deviation in the furnace when firing at the firing temperature shown in Table 1 is within the range of ±5°C. In addition, the proportions of Al, Si, Mn and Mo are the same within the error range in the input amount and after firing.
[0056]
Table 1
[0057] (Morphological observation) For the sintered bodies of Examples 1 to 8 and Comparative Examples 1 to 5, the sintered bodies were ground using a cross-section polisher (abbreviated as CP) (manufactured by JEOL Ltd., IB-15000CP), and the cross-section obtained was observed using a field emission scanning electron microscope (SEM) (manufactured by JEOL Ltd., JSM-7000F) to obtain an SEM image. A gold film was set on the cross-section of the sintered body by sputtering, and the cross-section was observed using a reflected electron model. The acceleration voltage was 15.0 kV and the magnification was 5000 times. The phases contained in each sintered body were confirmed by the image. Furthermore, for the SEM image of each sintered body, a histogram with the horizontal axis being the brightness value (0 to 255) and the vertical axis being the frequency of occurrence is shown. Next, the threshold value of the brightness value for dividing each phase of the void, the first glass phase, the aluminum oxide phase, and the second glass phase was determined with reference to the SEM image. After the threshold value is determined, the integral value of the frequency in each partition of the first glass phase and the second glass phase is calculated. The ratio of the integrated value of each of the first glass phase and the second glass phase to the integrated value of the frequency of occurrence in the total brightness value was taken as the content ratio (area %) of each of the first glass phase and the second glass phase. ImageJ was used as image processing software. The results are shown in Table 2.
[0058] (Determination of strength and Young's modulus) The sintered bodies of Examples 1 to 8 and Comparative Examples 1 to 5 were tested for flexural strength at room temperature in accordance with the three-point bending test of JIS R1601. In addition, the Young's modulus was tested in accordance with the three-point bending test method of JIS R1602 using a strain gauge. The results are shown in Table 2. Fig.10 .
[0059]
Table 2
[0060] As shown in Table 2, in the sintered bodies of Examples 1 to 8, the presence of two glass phases, the first glass phase and the second glass phase, was confirmed. The content ratio of the first glass phase in the sintered body was 0.1 area % to 7.5 area %. The content ratio of the second glass phase was 14.8 area % to 26.1 area %. In contrast, in the sintered bodies of Comparative Examples 1 to 5, the first glass phase did not appear, and the content ratio of the second glass phase was 12.3 area % to 33.3 area %. In addition, the strength of the sintered bodies of Examples 1 to 8 was 366 MPa or more, and the Young's modulus was 275 GPa or less.
[0061] Fig.10 This is a graph showing the distribution of the Young's modulus and the flexural strength of the sintered bodies of Examples 1 to 8 and Comparative Examples 1 to 5. Fig.10 The horizontal axis represents Young's modulus, and the vertical axis represents flexural strength. Fig.10As shown, the sintered bodies of Examples 1 to 8 are distributed in the upper left of the graph (low Young's modulus and high bending strength) compared with the sintered bodies of Comparative Examples 1 to 5. That is, when the Young's modulus is the same, the sintered bodies of the Examples have higher bending strength than the sintered bodies of the Comparative Examples. In addition, when the bending strength is the same, the sintered bodies of the Examples have lower Young's modulus than the sintered bodies of the Comparative Examples. Fig.10 As shown, in the graph in which the y-axis is the bending strength (MPa) and the x-axis is the Young's modulus (GPa), the sintered bodies of Examples 1 to 8 all have coordinates of bending strength and Young's modulus between the straight line y=1.7x+18 and the straight line y=1.7x+168. In contrast, the sintered bodies of Comparative Examples 1 to 5 all have coordinates of bending strength and Young's modulus outside the range divided by these two straight lines. If the ratio of the value of the bending strength (MPa) to the value of the Young's modulus (GPa) is calculated, it is 1.92 to 2.26 in Examples 1 to 8, compared to 1.48 to 1.66 in Comparative Examples 1 to 5. Based on these results, it is confirmed that the sintered bodies of Examples 1 to 8 have both high strength and low Young's modulus.
[0062] (Elemental Analysis) For the sintered bodies of Comparative Examples 2 and 4 and Examples 2, 4, 6, and 8, multiple positions where glass phases existed were selected in the obtained SEM images, and point analysis was performed using EDS (manufactured by JEOL Ltd., JSM-7000F). The sintered bodies of the Comparative Examples had one glass phase, and multiple positions where the glass phase existed were selected. The sintered bodies of the Examples had two glass phases, and the two glass phases were selected respectively.
[0063] Figure 4 Comparative Example 2 Figure 5 Comparative Example 4 Figure 6 Example 2 Figure 7 Example 4, Figure 8 Example 6 Fig. 9 The SEM image and analysis image (image showing the position of element analysis in the SEM image) of Example 8 are shown. The position of element analysis is indicated by a cross mark. For each example, two fields of view were analyzed. Tables 3 to 5 show the analysis results according to Figures 4 to 9 The elemental analysis results at each position shown are as follows: SiO 2 The content ratio (mass %) of SiO and MnO in the analysis values in Tables 3 to 5 is 2 The values of Si and MnO are calculated by converting the mixing ratio of Si and Mn elements into SiO 2 , MnO, SiO 2 , and MnO do not total 100%.
[0064]
Table 3
[0065] like Figure 4 As shown in Table 3, in Comparative Example 2, a glass phase was observed in the SEM image. In addition, as shown in Table 3, in Comparative Example 2, SiO 2 Relative to SiO 2 The total content ratio of MnO is 42.2 mass % to 49.3 mass %.
[0066] like Figure 5 As shown in Table 3, in Comparative Example 4, a glass phase was observed in the SEM image. In addition, as shown in Table 3, in Comparative Example 4, SiO 2 Relative to SiO 2 The total content ratio of MnO is 43.7 mass % to 49.9 mass %.
[0067]
Table 4
[0068] like Figure 6 As shown in Table 4, in Example 2, two glass phases were observed in the SEM image. In addition, as shown in Table 4, in Example 2, SiO 2 Relative to SiO 2 The total content of SiO and MnO is 52.4 mass % to 57.0 mass %. SiO 2 Relative to SiO 2 The total content of Si and MnO is 76.0 mass %.
[0069] like Figure 7 As shown in Table 4, in Example 4, two glass phases were observed in the SEM image. In addition, as shown in Table 4, in Example 4, SiO 2 Relative to SiO 2 The total content of SiO and MnO is 54.4% to 59.0% by mass. SiO 2 Relative to SiO 2 The total content of Mn and MnO is 89.0 mass %.
[0070]
Table 5
[0071] like Figure 8 As shown in Table 5, in Example 6, two glass phases were observed in the SEM image. In addition, as shown in Table 5, in Example 6, SiO 2 Relative to SiO 2 The total content of SiO and MnO is 51.4 mass % to 56.6 mass %. SiO 2 Relative to SiO 2 The total content ratio of Mn and MnO is 77.5 mass % to 91.6 mass %.
[0072] like Fig. 9 As shown in Table 5, in Example 8, two glass phases were observed in the SEM image. In addition, as shown in Table 5, in Example 8, SiO 2 Relative to SiO 2 The total content of SiO and MnO is 49.3 mass % to 57.3 mass %. SiO 2 Relative to SiO 2 The total content ratio of MnO is 81.7 mass % to 93.8 mass %.
[0073] exist Fig.11 The SiO at each measurement position of Comparative Examples 2, 4 and Examples 2, 4, 6, and 8 was 2 Relative to SiO 2 The total content ratio of MnO is shown in a graph. Fig.11 As shown, in Comparative Examples 2 and 4, at all the measurement positions, SiO 2 Relative to SiO 2 The total content of SiO and MnO was between 40 mass % and 60 mass %, and only the second glass phase was formed. 2 Relative to SiO 2 The second glass phase and SiO have a total content of 40 mass % to 60 mass % with MnO. 2 Relative to SiO 2 The first glass phase, in which the total content ratio with MnO exceeds 75 mass %, exists clearly and separately.
[0074] It should be understood that the embodiments and examples disclosed herein are illustrative in all aspects and are not restrictive in any aspect. The scope of the present disclosure is not defined by the above description but by the claims, and is intended to include all changes within the meaning and scope equivalent to the claims. Description of Reference Numerals
[0075] 1 crystal oscillator, 101 package body, 100 base, 110 substrate portion, 112 frame portion, 600 metallization layer, 100 sintered body, 11 alumina phase, 21 first glass phase, 31 second glass phase, 51 gap.
Claims
1. A sintered body, characterized in that: Comprising Al2O3, SiO2 and MnO, the sintered body comprises: The main crystalline phase is composed of Al2O3; First glass phase; as well as a second glass phase having a composition different from that of the first glass phase, The first glass phase is a phase comprising SiO2 and MnO, The second glass phase is a phase comprising SiO2 and MnO, The content ratio of SiO 2 in the first glass phase relative to the total of SiO 2 and MnO is greater than the content ratio of SiO 2 in the second glass phase relative to the total of SiO 2 and MnO.
2. The sintered body according to claim 1, wherein The first glass phase is a phase in which the content ratio of SiO2 relative to the total of SiO2 and MnO is 65 mass % or more and less than 100 mass %, The second glass phase is a phase in which the content ratio of SiO 2 relative to the total of SiO 2 and MnO is 35 mass % or more and less than 65 mass %.
3. The sintered body according to claim 1 or 2, wherein In the sintered body, The total content of SiO2 and MnO relative to the total mass of the sintered body is 11.0 mass % or more and 30.0 mass % or less, The content ratio of SiO 2 to the total of SiO 2 and MnO is 54.0 mass % or more and 66.6 mass % or less.
4. The sintered body according to claim 1 or 2, wherein A scanning electron microscope image of the sintered body is binarized to obtain an image, wherein the area ratio of the first glass phase obtained from the image is 0.1 area % or more and 10 area % or less, The area ratio of the second glass phase obtained from the image is 10 area % or more and 30 area % or less.
5. The sintered body according to claim 1 or 2, wherein The sintered body has a strength of 300 MPa to 660 MPa, a Young's modulus of 170 GPa to 290 GPa, In the graph with the y-axis representing strength in MPa and the x-axis representing Young's modulus in GPa, the coordinates of the strength and Young's modulus of the sintered body exist between the straight line y=1.7x+18 and the straight line y=1.7x+168.
Citation Information
Patent Citations
Ceramic matrix and method for producing same
CN107001147A
High-strength high-modulus magnesium-aluminum-silicon system microcrystalline glass material and preparation method thereof
CN110357435A
Sintered body, circuit component, and method for manufacturing sintered body
CN110997597A
Alumina sintered compact, its production method, and wiring board
JP2003104772A
Ceramic matrix and method for producing same
WO2016098767A1
